1976
DOI: 10.1042/bj1600357
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of renal proximal tubules after mercuric chloride injury is accompanied by increased binding of aminoacyl-transfer ribonucleic acid

Abstract: Homogenates of rat kidney cortex obtained 1,3 or 14 days after a single injection of HgCl2 were used to prepare the post-microsomal pH5 supernatant fraction. The activity of this fraction for peptide synthesis from [14C]phenylalanyl-tRNA was significantly increased at 1 and 3 days, at which time the proximal tubules are regenerating [Cuppage & Tate (1967) Am. J. Pathol. 51, 405-429]. This increased activity could not be attributed to a decreased inhibitory activity, but was due to an increased aminoacyl-tR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This proposed mechanism is supported by the immunohistochemical finding of sustained presence of cytoplasmic and nuclear PSA-1 in the tubular epithelial cells in the autoprotected mice. Protein translation elongation factor is known to increase protein synthesis during repopulation of proximal tubules after injury by a single injection of HgCl 2 (38). In our study, we found that in lowdose and autoprotected groups, translation elongation factor was moderately downregulated, whereas with a lethal dose alone it was substantially underexpressed (Table 3), suggesting inhibition of essential protein synthesis needed for cell division and tubular repopulation of epithelial cells following high dose alone-induced injury.…”
Section: Discussionmentioning
confidence: 48%
“…This proposed mechanism is supported by the immunohistochemical finding of sustained presence of cytoplasmic and nuclear PSA-1 in the tubular epithelial cells in the autoprotected mice. Protein translation elongation factor is known to increase protein synthesis during repopulation of proximal tubules after injury by a single injection of HgCl 2 (38). In our study, we found that in lowdose and autoprotected groups, translation elongation factor was moderately downregulated, whereas with a lethal dose alone it was substantially underexpressed (Table 3), suggesting inhibition of essential protein synthesis needed for cell division and tubular repopulation of epithelial cells following high dose alone-induced injury.…”
Section: Discussionmentioning
confidence: 48%